2018
DOI: 10.32014/2018.2518-1491.20
|View full text |Cite
|
Sign up to set email alerts
|

Development of Composite Materials by Combustion Synthesis Method for Catalytic Reforming of Methane to Synthesis Gas

Abstract: Известия Национальной академии наук Республики Казахстан 2 NAS RK is pleased to announce that News of NAS RK. Series of chemistry and technologies scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Results of physical and chemical research of catalysts prepared confirmed literature data [6,13,14,[27][28][29][30].…”
Section: 2019supporting
confidence: 81%
See 1 more Smart Citation
“…Results of physical and chemical research of catalysts prepared confirmed literature data [6,13,14,[27][28][29][30].…”
Section: 2019supporting
confidence: 81%
“…The catalysts-neutralizers of the exhaust (catalytic converter, an afterburner) are the mandatory option for all cars in the developed countries. Today, the monolithic metal blocks are considered as the most appropriate catalysts used for the solution of environmental problems [13][14][15][16][17]. High heat conductivity of metal carriers provides the good thermoregulation preventing an overheat of catalysts and interfacing constructional details.…”
Section: Issn 2224-5278mentioning
confidence: 99%
“…Natural and petroleum gases are the most important alternative sources of raw materials that can in the long run compete with oil. Of particular relevance for countries rich in this type of raw material is the problem of the rational use of alkanes in their composition [1][2][3][4][5]. Kazakhstan has significant oil and gas reserves.…”
Section: Liquefied Petroleum Gas As Raw Materials For the Production mentioning
confidence: 99%
“…Biodiesel plants are not capital-intensive plants [20][21][22][23]. The majority of the cost is expended for production of biodiesel from the oil.…”
Section: Introductionmentioning
confidence: 99%